Russian Language as A Foreign Language in Medical Universities - Khamrayeva Mavlyuda Djurayevna (Genius Journals, 2021)
The article gives a brief overview of foreign language teaching methods. At the same time, new methods of teaching Russian as a foreign language in higher education are presented and analyzed with the help of examples
Keywords: Higher education; foreign language teaching methods; communicative tasks; speech